NEW RECORDS OF KING CRABS (DECAPODA, ANOMURA, LITHODIDAE) FROM SOUTHERN BRAZIL - Lianos, L. [UNESP]; Mollemberg, M. C.; Lima, D. J.M. [UNESP]; Santana, W. [UNESP] (My University, 2018)
Until now only six species of lithodids have been found occasionally in the Brazilian coast. Most king crabs are accidentally caught during fisheries targeting other species. Herein we report new records for Lithodes confundens and Neolithodes aff. asperrimus from the south of Brazil, from the states of Rio Grande do Sul and Santa Catarina, respectively. Lithodes confundens is found in the western Atlantic with a previous northern limit in the Province of Buenos Aires, Argentina. Neolithodes aff. asperrimus is known to occur only along the western coast of Africa in the eastern Atlantic and this is the first record of the species in the western Atlantic.
Keywords: distribution; eastern Atlantic; Lithodoidea; South America; western Atlantic